2017
DOI: 10.1093/mnras/stx277
|View full text |Cite
|
Sign up to set email alerts
|

Abell 2744: too much substructure for ΛCDM?

Abstract: The massive substructures found in Abell 2744 by Jauzac et al. (2016) present a challenge to the cold dark matter paradigm due to their number and proximity to the cluster centre. We use one of the biggest N-body simulations, the Millennium XXL, to investigate the substructure in a large sample of massive dark matter haloes. A range of effects which influence the comparison with the observations is considered, extending the preliminary evaluation carried out by Jauzac et al. (2016). There are many tens of halo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 50 publications
2
45
0
Order By: Relevance
“…The detection of this hardening requires the ability to identify subhalos in the inner regions of the host halo, which hbt+ does, but which subhalo finders that work in configuration space alone have difficulty identifying. Recent lensing observations of galaxy clusters have resulted in reports of discrepancies in the observed subhalo distribution compared to that of ΛCDM predictions, including the excess of massive subhalos reported by Jauzac et al (2016) and Schwinn et al (2017) and the more concentrated subhalo radial distribution reported by Natarajan et al (2017). These discrepancies can be explained, at least in part, by the blending problem present in the Millennium-XXL and Illustris subfind catalogues used in their comparisons.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The detection of this hardening requires the ability to identify subhalos in the inner regions of the host halo, which hbt+ does, but which subhalo finders that work in configuration space alone have difficulty identifying. Recent lensing observations of galaxy clusters have resulted in reports of discrepancies in the observed subhalo distribution compared to that of ΛCDM predictions, including the excess of massive subhalos reported by Jauzac et al (2016) and Schwinn et al (2017) and the more concentrated subhalo radial distribution reported by Natarajan et al (2017). These discrepancies can be explained, at least in part, by the blending problem present in the Millennium-XXL and Illustris subfind catalogues used in their comparisons.…”
Section: Discussionmentioning
confidence: 96%
“…The deficiency of massive subhalos near the centre of the host halo in catalogues constructed using subfind explains, at least in part, the disagreement noted by Schwinn et al (2017) and Natarajan et al (2017) between the distrubtion of subhalos identified using subfind in ΛCDM simulations and the distribution of subhalos inferred from lensing studies in galaxy clusters. Mao et al (2017) have argued that the mismatch between the simulation result of Millennium-XXL (Angulo et al 2012) and the lensing results of Jauzac et al (2016); Schwinn et al (2017) is also affected by the use of different masses in the comparison: subfind masses in the simulation but projected aperture masses from lensing that also include mass contributions from the host.…”
Section: Direct Comparison With Subfindmentioning
confidence: 93%
See 2 more Smart Citations
“…The high concentrations and large Einstein radii found for several massive clusters have been previously claimed to challenge ΛCDM Broadhurst & Barkana 2008), although updated analyses (and account of projection biases) have alleviated this tension Umetsu et al 2016). In a similar fashion, the amount of substructure within massive clusters can also be compared to numerical simulations and expectations from ΛCDM (Jauzac et al 2016;Schwinn et al 2017). Given its extreme properties, PLCKG287 is another useful laboratory for similar studies.…”
Section: Resultsmentioning
confidence: 99%